COREGISTRATION OF DSM AND 3D POINT CLOUDS ACQUIRED BY A MOBILE MAPPING SYSTEM - RIDENE, TAHA; GOULETTE, FRANÇOIS (Boletim de Ciências Geodésicas, 2009)
The development of 3D mapping databases is a matter of increasing interest. Databases have recently been developed at different scales (national, European, international) and to meet different needs. Such development has been made possible by the implementation of efficient 3D mapping technologies. 3D mapping strategies are based on multi-sensor data fusion usually performed after a preprocessing step that includes registration and filtering. In this paper, we present our work on registration methods applied to solve problems in 3D urban environment representations issued from a Mobile Mapping System. We improve the stability of convergence, the computation time and handle heterogeneous data sets in various scenarios.